Photothermy-strengthened photocatalytic activity of polydopamine-modified metal-organic frameworks for rapid therapy of bacteria-infected wounds. (30th January 2021) - Han, Donglin; Li, Yuan; Liu, Xiangmei; Yeung, Kelvin Wai Kwok; Zheng, Yufeng; Cui, Zhenduo; Liang, Yanqin; Li, Zhaoyang; Zhu, Shengli; Wang, Xianbao; Wu, Shuilin
Graphical abstract: After modification of PDA coating, the photothermal and photocatalytic properties of MOF-PDA nanoparticles are both enhanced. Abstract: Herein, a metal-organic framework (MOF) was modified using polydopamine (PDA) to develop the MOF-PDA as a photoresponsive bacteria-killing agent under 660 nm light irradiation. The modification using PDA led to the production of not only more heat, but also much more 1 O2 . This is because the PDA could interact with the porphyrin ring of the MOF through π-π interaction and the charge transfer between PDA and the MOFs decreases the energy of the band of hybrid nanoparticles. In addition, greater levels of hyperthermia induced by PDA modification accelerated the charge transfer, which significantly strengthened the photocatalytic performance of MOF-PDA. Furthermore, after modification, the light absorbance and water dispersibility of nanoparticles were both enhanced; both are important for the improvement of photocatalytic and photothermal properties. Consequently, MOF-PDA exhibited the highly effective antibacterial efficacy of 99.62 % and 99.97 % against Staphylococcus aureus and Escherichia coli, respectively, under 20 min 660 nm light irradiation.